A modeling study on utilizing ultra-thin inorganic HTLs in inverted p–n homojunction perovskite solar cells. (1st January 2021) - Maram, Daniyal Khosh; Haghighi, Maryam; Shekoofa, Omid; Habibiyan, Hamidreza; Ghafoorifard, Hassan
Highlights: A p-n homojunction perovskite solar cell. Inverted perovskite solar cell with ultra-thin inorganic HTLs. Inverted p-n homojunction perovskite solar cell with non-toxic inorganic HTL. CuAlO2, a promising p-type inorganic material as a hole transport layer. Abstract: Homojunction perovskite is used as a promising absorber layer in perovskite solar cells. In order to have p-n homojunction perovskite, we are able to induce n-type or p-type doping, thanks to controlling the stoichiometry of the perovskite precursors. In a p-n homojunction perovskite layer, the built-in electric field promotes oriented transport of the photo-induced carriers, thus reduces the carrier recombination losses. In this paper, by combining the modeling results of two basic structures, which are also compared with similar reported experimental data for their validation, an inverted structure with p-n homojunction MAPI perovskite and ultra-thin HTL film is suggested. Simulation results show that replacing the intrinsic MAPI perovskite with p-n homojunction MAPI perovskite leads to a 13% increase of efficiency in the inverted structure. Also, by investigating the various p-type inorganic materials, we propose CuAlO2 as a promising inorganic hole transport material, and its utilization for the inverted p-n homojunction perovskite solar cell delivers efficiency of 16.48%. We demonstrate that using the structure with homojunction perovskite is an effective approach, beyond existing planar structures, to achieve a highly efficient solar cell with reduced carrier recombination losses.